Auditors in the digital age: a systematic literature review - Diogo Leocádio; Luís Malheiro; João Carlos Gonçalves dos Reis (Digital Transformation and Society)
Purpose – This study examines the dynamics of innovative auditing practices in the digital age, with a specific focus on auditor competencies. Within this scope, we highlight the necessity of redefining auditing practices and the essential adaptation required from auditors. The primary objective is to understand comprehensively how auditor competencies can be strengthened to meet the challenges posed by innovative audit practices. Design/methodology/approach – A Systematic Literature Review (SLR) was conducted to explore this theme, ensuring rigor and credibility in the outcomes. The results emphasize the importance of auditors strengthening professional competencies, embracing technological agility, and promoting ongoing professional development initiatives. Findings – The triadic framework comprising—Auditor, Auditing Practices, and Digital Audits— forms the basis for innovative audit practices. This manuscript further discusses the transition of advanced technologies, laying the groundwork for the evolution of auditing practices. Through a systematic assessment of the literature, this study develops a framework for innovative, ethically driven, and effective auditing practices, ensuring the occupation's relevance and value. Future investigations should focus on the ethical implications of automation in auditing practices and develop innovative frameworks tailored to diverse organizational contexts. Originality/value – The study addresses a contemporary issue by examining the evolving nature of auditing practices considering digital transformation. Practical implications highlight the enhancement of auditor roles in digital transformation, covering ethics, technological adaptation, and continuous development to uphold the profession's integrity. This focus acknowledges the changing dynamics of business and the growing role of technology in auditing processes.